2001
DOI: 10.18388/abp.2011_2231
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana Nudix hydrolase AtNUDT7 forms complexes with the regulatory RACK1A protein and Ggamma subunits of the signal transducing heterotrimeric G protein.

Abstract: Arabidopsis thaliana AtNUDT7 Nudix pyrophosphatase hydrolyzes NADH and ADP-ribose in vitro and is an important factor in the cellular response to diverse biotic and abiotic stresses. Several studies have shown that loss-of-function Atnudt7 mutant plants display many profound phenotypes. However the molecular mechanism of AtNUDT7 function remains elusive. To gain a better understanding of this hydrolase cellular role, proteins interacting with AtNUDT7 were identified. Using AtNUDT7 as a bait in an in vitro bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The data indicates that GPA1does not directly interact with RACK1 in any of the implemented assays (YTH, suYTH, Co-IP, in planta BiFC, SFLC, etc.). Moreover, although the interaction between RACK1 and the AGG1/AGG2 subunits was not analyzed in these reports, it was previously shown that AtRACK1A consistently interacted with both AGG1 and AGG2 using in vitro (pull-down), and in vivo (YTH and BiFC in protoplasts) assays (Olejnik et al, 2011 ). Therefore, the accumulating evidence leads to the notion that plant RACK1 can form complexes with the Gβ and Gγ subunits, but not with Gα.…”
Section: Rack1-interacting Ligands Some Solid Evidence and Some Enimentioning
confidence: 97%
See 2 more Smart Citations
“…The data indicates that GPA1does not directly interact with RACK1 in any of the implemented assays (YTH, suYTH, Co-IP, in planta BiFC, SFLC, etc.). Moreover, although the interaction between RACK1 and the AGG1/AGG2 subunits was not analyzed in these reports, it was previously shown that AtRACK1A consistently interacted with both AGG1 and AGG2 using in vitro (pull-down), and in vivo (YTH and BiFC in protoplasts) assays (Olejnik et al, 2011 ). Therefore, the accumulating evidence leads to the notion that plant RACK1 can form complexes with the Gβ and Gγ subunits, but not with Gα.…”
Section: Rack1-interacting Ligands Some Solid Evidence and Some Enimentioning
confidence: 97%
“…More recently, Olejnik et al ( 2011 ) found that AtRACK1A binds to AtNUDT7. AtNUDT7 is a pyrophosphatase that hydrolyzes NADH and ADP-ribose in vitro , and plays a role in the response to biotic and abiotic stress.…”
Section: Rack1 Also Appears On the Scene Of Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such examples include GTPases and R proteins, which function as signaling components, rather than modulators of cellular GTP and ATP levels, respectively (Li and Zhang, 2004;Takken and Tameling, 2009). Interestingly, At-NUDT7 was reported to interact with 14-3-3 proteins (Olejnik et al, 2009), RACK1A and the gamma subunit of G proteins (Olejnik et al, 2011), but the physiological effects of these interactions are still unknown. Some point mutations in AtNUDT7 may change its quaternary structures and hamper its interaction with other proteins (Olejnik et al, 2009), but the physiological consequences of these point mutations have not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolases and oxidoreductases covered 16.5 and 12.5% of the interactors, respectively. A. thaliana Nudix hydrolase AtNUDT7 plays important role in cellular response to diverse biotic and abiotic stresses by forming complexes with RACK1A protein and Gγ subunits of the signal transducing heterotrimeric G‐protein . Certain oxidoreductase proteins are located at the membrane/cytoskeleton area where they act as adaptors to receive signals from the cell surface .…”
Section: List Of Nucleotide‐dependent Rga1 Interactors Thirty Two Inmentioning
confidence: 99%